0221 Creating Student Aspih (saspih): Proposed Business Platform Model - Establishing A Viable, Resilient And Accountable Student Branch Of Aspih. (1st November 2014) - Gopal, Alan; Pendleton, Matthew; Cox, David
Abstract : Background and context: Establishing a special interest group of the Association for Simulated Practice in Healthcare (ASPiH) 1 aimed at recruitment, retention and development 2 of undergraduate students to ASPiH (Student ASPiH/SASPiH) would benefit both ASPiH and UK undergraduate healthcare professionals involved in simulated practice in healthcare. For this we propose a business platform model 3, 4 to maximise potential advantages for all involved. 5 Traditional student-centric structures often suffer from variability over the personnel recruited, and resources available; they are subject to lapsing or losing momentum from rapid turnover of personnel, especially with the ever-increasing demands of completing a professional degree. In this climate of fiscal responsibility, a business orientated model offers a viable way of ensuring resilience and maximising the potential benefits on both sides of the partnership. Methodology: Utilising a relatively shallow hierarchy of a student national committee with direct senior supervision, the main aims of the SASPiH committee would be the creation of educational products (i.e. a platform for innovation 6 ) to offer student-specific incentives for joining ASPiH and acting as a hub for student ventures. A product would be anything of value professionally such as; regional events aimed at exposing students to simulation-based medical education, opportunities such as a medical student elective packages in simulated practice 7 and online resources. Anticipated outcomes: With guidance from senior members of ASPiH over development and implementation of products, each student-driven venture would benefit from action-based entrepreneurial education 2 and be expected to present results of their completed project at annual ASPiH conference, while adding the product to their portfolios 8 and the repertoire of SASPiH for future use while increasing undergraduate recruitment. Potential impact: The model we are proposing is designed to recruit students, develop their interests and abilities 2 to provide simulation-based medical education, reward their innovations 8 and contribute to ASPiH is a transparent, accountable way. 5 References: ASPiH. About Us [Internet]. ASPiH; 2014 [cited 2014 Sept 1]. Available: http://www.aspih.org.uk/about-us/ Rasmussen EA, Sorheim R. Technovation, 2006;26(2):185–194 Davidsson P, Klofsten M. Journal of Small Business Management, 2003;41(1):1–26 Hedman J, Kalling T. European Journal of Information Systems, 2003;12:49–59 Chesborough H. Strategy & Leadership, 2007;35(6):12–17 Gawer A, Cusumano MA. Platform Leadership. 2nd Ed. Boston, MA: Harvard Business School Press;2002 Gopal A, Purva M. Poster session presented at: 2014 SCSN-ASPiH Scottish Symposium; 2014 April23-24; Uaill, Glasgow, UK Lamki N, Marchand M. Sultan Qaboos Univ Med J. 2006;6(1):6–12